2022
DOI: 10.3389/fimmu.2022.999163
|View full text |Cite
|
Sign up to set email alerts
|

Spectral flow cytometry cluster analysis of therapeutic donor lymphocyte infusions identifies T cell subsets associated with outcome in patients with AML relapse

Abstract: Identification of immune phenotypes linked to durable graft-versus-leukemia (GVL) response following donor lymphocyte infusions (DLI) is of high clinical relevance. In this prospective observational study of 13 AML relapse patients receiving therapeutic DLI, we longitudinally investigated changes in differentiation stages and exhaustion markers of T cell subsets using cluster analysis of 30-color spectral flow cytometry during 24 months follow-up. DLI cell products and patient samples after DLI were analyzed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…While there are far too many to list, we refer the reader to several examples of non-clinical assays with human specimens. [20][21][22][23][24][25][26] The above method-comparison studies provide strong preliminary evidence that spectral flow cytometers are likely functionally equivalent to conventional flow cytometers but are superior in the sense that they can perform high-dimensional assays in a single-tube format that otherwise requires 4 separate tubes on current 10-to-12-color conventional flow cytometers. It is critical that comprehensive validation studies be published in reputable peer-reviewed journals with comparisons against regulatory agency-approved predicate conventional flow cytometers.…”
Section: Clinical Applications Of Spectral Flow Cytometrymentioning
confidence: 85%
See 1 more Smart Citation
“…While there are far too many to list, we refer the reader to several examples of non-clinical assays with human specimens. [20][21][22][23][24][25][26] The above method-comparison studies provide strong preliminary evidence that spectral flow cytometers are likely functionally equivalent to conventional flow cytometers but are superior in the sense that they can perform high-dimensional assays in a single-tube format that otherwise requires 4 separate tubes on current 10-to-12-color conventional flow cytometers. It is critical that comprehensive validation studies be published in reputable peer-reviewed journals with comparisons against regulatory agency-approved predicate conventional flow cytometers.…”
Section: Clinical Applications Of Spectral Flow Cytometrymentioning
confidence: 85%
“…In addition to these studies, there are many examples in the research literature where spectral flow cytometry assays have been used successfully to immunophenotype human blood, bone marrow, or lymph nodes. While there are far too many to list, we refer the reader to several examples of non‐clinical assays with human specimens 20–26 …”
Section: Clinical Applications Of Spectral Flow Cytometrymentioning
confidence: 99%
“…Beyond conventional gating, we performed an unsupervised cluster analysis ( 26 ) of the infused CAR T-cell product (n=11) as well as across all available samples (n=29). As described in the Methods section cells were separated into 15 distinct clusters for the analysis of the infused CAR T-cell products ( Figure 1F ) and 20 distinct clusters in the case of all samples analysis ( Supplementary Figure S2A ).…”
Section: Resultsmentioning
confidence: 99%
“…Adoptive cell transfer (ACT) is one of the major immunotherapeutic strategies in AML. Compared to terminally differentiated T cells, donor lymphocyte infusions (DLI) in relapsed AML patients with higher proportions of early-differentiated memory T cells showed superior durability and anti-tumor activity ( 21 ). In addition, early-differentiated memory T cells expressed higher levels of immune checkpoints compared relapsed to CR AML patients after allo-HSCT ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…In AML, CD8 Tn-derived donor cells effectively combated AML blasts in immunodeficient mice ( 35 ). Donor lymphocyte infusions (DLI) with cell products containing higher CD4 and CD8 Tn proportions were associated with a longer-term remission in AML ( 21 ). Consistently, our study demonstrated that increased BM CD8 Tn at diagnosis independently predicted both favorable RFS and EFS in AML.…”
Section: Discussionmentioning
confidence: 99%